A 17-Years Old Man of Colitis Tuberculosis with Fistula Perianal - Paulus Kusnanto; Marcellus Simadibrata; Ari Fahrial Syam; Achmad Fauzi; Murdani Abdullah; Dadang Makmun; Chudahman Manan; Daldiyono Daldiyono; Abdul Aziz Rani; Ening Krisnuhoni (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2008)
Tuberculosis (TB) remains to be one of the most common problems in developing countries such as Indonesia. It can involve many organs including gastrointestinal tracts. Colonic tuberculosis is an ancient disease and has long been recognized. However, it is sometimes difficult to make early diagnosis due to its nonspecific signs and symptoms. Perianal granulomas or perianal fistula presents some degree of diagnostic difficulty. A spectrum of diseases can produce granulomas in perianal region and perineum. Most are infectious or inflammatory diseases. Standard histological diagnosis often less significant to clarify the etiology and treatment will vary from one to another disease entity. In this report, we present a case 17-years old man with colitis TB and fistula perianal, in which the initial diagnostic workup suggested Crohn’s disease. Mantoux test, Acid Fast Bacilli test on fecal examination and polymerase chain reaction analysis revealed negative result. The chest X-ray was normal; while the fistulography X-ray: revealed 2 orifices in rectosigmoid area. The colonoscopy revealed mucosa edema with ulceration in rectosigmoid and pedincular polyp in the caecum. Initial colonoscopy diagnosis was Crohn’s disease with differential diagnosis colitis ulcerative, colitis TB, colitis infection. results of direct or post homogenizes examination (Ziel–Nielsen staining) revealed that no acid-fast bacilli was found. Multiple biopsies were done, which indicated  mucosa edema with ulceration in rectosigmoid area, pedincular polyp in the caecum, and surrounded by fistula perianal; while histopathological examination showed inflammatory-caseating-epithelioid-granulomas and giant cells (Langhans datia cell) caused by tuberculosis. It highlights the need for awareness of intestinal TB along with the differential diagnosis of chronic intestinal disease. Standard regimen of antituberculosis treatment was given and the patient showed good clinical response. Keywords: Crohn’s disease, caseating epithelioid granuloma, giant cell, colitis TB, perianal fistula